E-Hospital Management & Hospital Information System – Use of IOT - Gunathilake C.D.; Theebanraj U.; Ananthan Y.; Kanishkar R.; D.I. De Silva; Samitha Vidhanarachchi (International Journal of Engineering and Management Research, 2022)
To operate successfully and efficiently, a healthcare institution needs high-quality data and information management. To say that many companies, organizations, or government agencies are critically dependent on the use of database systems for their success, especially in hospitals, would be an understatement. This work aims to develop an improved hospital information management system using an activity-based approach. This study presents an effective hospital information management system that can be used to handle patient information and its administration. This aims to solve the issues that the current hospital information system has with inappropriate data retention, erroneous reports, and time wastage when storing, processing, and retrieving information to increase the overall effectiveness of the medical facility. Express.JS, Mongo DB, React.JS, and Node.JS were used to create the system. The technology offers a crucial storage and retrieval platform for information in hospitals. Many tests have been carried on, and they are attached and discussed in the document.